Kearifan Lokal dalam Praktik Penangkapan Ikan pada Nelayan di Gampong Panggong Aceh Barat - Fitri Derminta Berutu; Alfa Safira; Irhamna Irhamna; Rodi Yansah; Nabila Tuzzakina; Zul Fazli; Rahmatullah Rahmatullah; Sopar Sopar (Jurnal Ilmu Sosial dan Humaniora, 2026)
Local wisdom in fishing is the knowledge, values, and customary rules passed down from generation to generation by fishing communities regarding the utilization of marine resources. This wisdom serves as a guide for fishermen so that fishing activities maintain the balance of nature and the sustainability of fishery resources. Panggong Village, located in the coastal area of Meulaboh, is a community engaged in daily fishing. However, fishing is not merely an economic endeavor; it also encompasses numerous cultural values and social norms. The purpose of this study is to identify forms of local wisdom in fishing practices and analyze the role of the Panglima Laot (leader of the sea) in the fishing community of Panggong Village. The method used in this study is qualitative with a descriptive approach. Qualitative research aims to explore in-depth social phenomena that emerge within the community, particularly regarding the contribution of local wisdom to fishing practices by fishermen. The results of this study indicate that local wisdom among Panggong fishermen is still preserved, as evidenced by fishing activities, social relationships, the existence of the Panglima Laot (leader of the sea) customary institution, fishing gear, and customary regulations at sea.